Compliance in antihypertensive therapy: analyses in scientific articles - Sarquis, Leila Maria Mansano; Dell'acqua, Magda Cristina Queiroz; Gallani, Maria Cecília Bueno Jayme; Moreira, Rosa Maria; Bocchi, Silvia Cristina Mangini; Tase, Terezinha Hideco; Pierin, Angela Maria Geraldo (Revista da Escola de Enfermagem da USP, 1998)
The aim of this study was to evaluate scientific articles published between 1991-1995, in order to identify the compliance in antihypertensive therapy. One hundred seven scientific articles were evaluated. The results showed that 68% were related to patient, 63% to pharmacological treatment, 62% general, 39% non pharmacological treatment, 34% organizational factors, and 8% related to desease. Compliance with antihypertensive therapy was the major challenge of hypertension management and to know how this aspect was focalized in scientific articles possible reduce non compliance in hypertension.